Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Direct resistive heating of a catalytic fixed-bed reactor for ethanol dehydration - Emre Turan; Robert Dieckmann; Michael Geske; Raoul Naumann d’Alnoncourt; Michael Bender; Johannes Bode; Benjamin Frank; Dina Zakgeym; Grigorios Kolios; Frank Rosowski (Chemical Engineering Journal, 2025)

Persistent organic pollutants and trace elements detected in New Zealand fur seals (long-nosed fur seal; Arctocephalus forsteri) from New South Wales, Australia, between 1998 and 2019 - Jane Hall; Susan Bengtson Nash; Anil Gautam; Hannah Bender; Benjamin J. Pitcher; Hamish McCallum; Christopher Doyle (Science of The Total Environment, 2023)

Fronto-striatal alterations correlate with apathy severity in behavioral variant frontotemporal dementia - Neeraj Upadhyay; Annika Spottke; Anja Schneider; Daniel C. Hoffmann; Ingo Frommann; Tommaso Ballarini; Klaus Fliessbach; Benjamin Bender; Hauke R. Heekeren; John Dylan Haynes; Michael Ewers; Emrah Düzel; et al. (Brain Imaging and Behavior, 2023)
Structural and functional changes in cortical and subcortical regions have been reported in behavioral variant frontotemporal dementia (bvFTD), however, a multimodal approach may provide deeper insights into the neural correlates of neuropsychiatric symptoms. In this multicenter study, we measured cortical thickness (CTh) and subcortical volumes to identify structural abnormalities in 37 bvFTD patients, and 37 age- and sex-matched healthy controls. For seed regions with significant structural changes, whole-brain functional connectivity (FC) was examined in a sub-cohort of N = 22 bvFTD and N = 22 matched control subjects to detect complementary alterations in brain network organization. To explore the functional significance of the observed structural and functional deviations, correlations with clinical and neuropsychological outcomes were tested where available. Significantly decreased CTh was observed in the bvFTD group in caudal middle frontal gyrus, left pars opercularis, bilateral superior frontal and bilateral middle temporal gyrus along with subcortical volume reductions in bilateral basal ganglia, thalamus, hippocampus, and amygdala. Resting-state functional magnetic resonance imaging showed decreased FC in bvFTD between: dorsal striatum and left caudal middle frontal gyrus; putamen and fronto-parietal regions; pallidum and cerebellum. Conversely, bvFTD showed increased FC between: left middle temporal gyrus and paracingulate gyrus; caudate nucleus and insula; amygdala and parahippocampal gyrus. Additionally, cortical thickness in caudal, lateral and superior frontal regions as well as caudate nucleus volume correlated negatively with apathy severity scores of the Neuropsychiatry Inventory Questionnaire. In conclusion, multimodal structural and functional imaging indicates that fronto-striatal regions have a considerable influence on the severity of apathy in bvFTD.

Statistical analysis of preclinical inter-species concordance of histopathological findings in the eTOX database - Peter S.R. Wright; Katharine A. Briggs; Robert Thomas; Graham F. Smith; Gareth Maglennon; Paulius Mikulskis; Melissa Chapman; Nigel Greene; Benjamin U. Phillips; Andreas Bender (Regulatory Toxicology and Pharmacology, 2023)

Retrospective analysis of the potential use of virtual control groups in preclinical toxicity assessment using the eTOX database - Peter S.R. Wright; Graham F. Smith; Katharine A. Briggs; Robert Thomas; Gareth Maglennon; Paulius Mikulskis; Melissa Chapman; Nigel Greene; Benjamin U. Phillips; Andreas Bender (Regulatory Toxicology and Pharmacology, 2023)

Dynamical downscaling projections of late twenty-first-century U.S. landfalling hurricane activity - Thomas R. Knutson; Joseph J. Sirutis; Morris A. Bender; Robert E. Tuleya; Benjamin A. Schenkel (Climatic Change, 2022)

Pattern of Cerebellar Atrophy in Friedreich’s Ataxia—Using the SUIT Template - Tobias Lindig; Benjamin Bender; Vinod J. Kumar; Till-Karsten Hauser; Wolfgang Grodd; Bettina Brendel; Jennifer Just; Matthis Synofzik; Uwe Klose; Klaus Scheffler; Ulrike Ernemann; Ludger Schöls (The Cerebellum, 2019)

Memory-related hippocampal functioning in ecstasy and amphetamine users - Benjamin Becker; Daniel Wagner; Philip Koester; Katja Bender; Christoph Kabbasch; Euphrosyne Gouzoulis-Mayfrank; Jörg Daumann (Psychopharmacology, 2013)